Ecological aspects of alcohol industry enterprises modernization at present stage of development - Havryshko, Marianna; Popovych, Olena; Yaremko, Halyna (Видавництво Львівської політехніки, 2020)
At the present stage of development, the entire world industry has faced the problem of rational use of renewable natural resources, in particular the most efficient ways of wastewater treatment and the use of accumulated waste in the production process as secondary raw material. In particular, the alcohol industry, as one of the components of food, medical, chemical and various industries, leads to the formation of a huge amount of waste, including wastewater. The food industry, like any other industry, has a negative impact on the environment. Water bodies are the most affected by the food industry. Almost the first place in terms of water consumption per unit of production is the production of alcohol. Consumption of large amounts of water leads to the formation of wastewater, which is highly polluted and adversely affects the environment. Due to the high chemical and biological consumption of oxygen, specific colour and odor, suspended solids, low pH value, the purification of such waste in the filtration fields, and discharge into water bodies is not possible. The purpose of our work is: 1) the analysis of the alcohol industry potential in Ukraine in recent years, and methods of waste disposal as a potential source for the development of bioenergy. 2) environmental aspects of the alcohol industry modernization at the present stage of development and implementation of modern wastewater treatment technologies.
Keywords: food industry; alcohol industry; waste; sewage; ecological safety; bioenergy; bioethanol; state regulation